Upaya Modernisasi Pendidikan Islam Pada Tingkat Sekolah Dasar dan Madrasah Ibtidaiyah - Aisyi, Rifdah Rihadatul; Munandar, Imam Maulana (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2024)
This study explores teachers' perceptions of the modernization of Islamic education at SD Al-Ittihadiyah Mamiyai Bromo, along with the efforts made by the teachers to implement this modernization in their teaching practices. Through qualitative research with a case study approach, data were collected through interviews, observations, and document analysis. The findings reveal that teachers' perceptions are divided; some view modernization as a positive step to improve the quality of education, embracing technology and interactive methods, while others express concerns about the potential erosion of Islamic values. The efforts to implement modernization include the use of technology in classrooms, the adoption of more interactive teaching methods, and the development of a curriculum relevant to current needs. Despite the enthusiasm for modernization, challenges such as balancing technological advancements with the preservation of religious values remain significant. This study contributes to the understanding of how modernization in Islamic education is approached in rural areas and provides insights for future educational policies.